Covert communication in UAV-assisted air-ground networks - Jiang, Xu (2022)
Unmanned aerial vehicle (UAV) assisted communication is a promising technique for future wireless networks due to its characteristics of low cost and flexible deployment. However, the high possibility of line-of-sight (LoS) air-ground channels may result in a great risk of being attacked by malicious users. Especially compared to the encryption and physical layer security that prevent eavesdropping, covert communication aims at hiding the existence of transmission, which is able to satisfy the more critical requirement of security. Thus, in this article, we focus on the covert communication issues of UAV-assisted wireless networks. First, the preliminaries of secure communications including encryption, physical layer security and covert communication are discussed. Then, current works and typical applications of UAV in covert communications are demonstrated. We then propose two schemes to enhance the covertness of UAV-assisted networks for some typical scenarios. Specifically, to improve the covert rate in UAV-assisted data dissemination, an iterative algorithm is proposed to jointly optimize the time slot, transmit power and trajectory. For the covertness of ground-air communication, a friendly jammer is employed to confuse the wardens, where the location of the jammer, the jamming power and the legitimate transmit power are jointly optimized. Numerical results are presented to validate the performance of these two proposed schemes. Finally, several challenges and promising directions are pointed out.